2010
DOI: 10.1161/circgenetics.110.957407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Variations in Syntaxin-Binding Protein-5 and Syntaxin-2 on von Willebrand Factor Concentration and Cardiovascular Risk

Abstract: Background Elevated von Willebrand Factor (VWF) plasma levels are associated with an increased risk of cardiovascular disease. A meta-analysis of genome wide association studies on VWF identified novel candidate genes, i.e. syntaxin-binding protein 5 (STXBP5) and syntaxin 2 (STX2), which are possibly involved in the secretion of VWF. We investigated whether VWF antigen levels (VWF:Ag), VWF collagen-binding activity (VWF:CB), and the risk of arterial thrombosis are affected by common genetic variations in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 18 publications
5
46
0
1
Order By: Relevance
“…STXBP5 also promoted platelet secretion and thrombosis in mice. Thus, our present data provide strong functional evidence for the regulatory role on circulating vWF and thrombosis by a candidate gene previously identified by GWAS (45)(46)(47)(48)70).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…STXBP5 also promoted platelet secretion and thrombosis in mice. Thus, our present data provide strong functional evidence for the regulatory role on circulating vWF and thrombosis by a candidate gene previously identified by GWAS (45)(46)(47)(48)70).…”
Section: Discussionsupporting
confidence: 68%
“…We also tested the effect of genetic variation on STXBP5 function. We knocked down STXBP5 in ECs and then rescued STXBP5 expression with either WT STXBP5 or the N436S STXBP5 variant, which is associated with altered vWF levels in humans (47). N436S STXBP5 inhibited vWF secretion more effectively than did WT STXBP5 (Supplemenin murine brain, supporting studies identifying a role for Stxbp5 in neurovesicle release (49,54).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…We have previously shown in a well-defined cohort of young patients with a first event of arterial thrombosis that genetic variation in STXBP5 is associated with VWF:Ag levels. 13,39 The LD between rs1221638:A4G and the SNP that had the highest significance in the previous meta-analysis is D′ = 0.90 and R 2 = 0.67. The fourth locus was marked by rs4981022:A4G, which is located in STAB2.…”
Section: Discussionmentioning
confidence: 94%
“…Genetic studies in cardiology have shown an increase in syntax-binding protein and syntaxin 2, which are possibly involved in the secretion of von Willebrand factor (VWF). Increased concentrations of VWF are associated with a higher cardiovascular disease risk (24). The studies performed on rats have shown an increase in BNP GATA4 binding activity in the heart that was brought about by a pressure overload in vivo via the endothelin-1 signalling molecule (7).…”
Section: Discussionmentioning
confidence: 99%